Bridging the Theory-Practice Gap: A Qualitative Portfolio Analysis of Consultancy-as-Pedagogy in Brand Management Education - Yoanita Alexandra; Boby Arinto; Rajesh Prettypal Singh (Yayasan Sinergi Kawula Muda, 2026)
In contemporary business education, a persistent